2009
DOI: 10.4161/cbt.8.9.8118
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of thymidilate synthase and p53 expression by HDAC inhibitor vorinostat resulted in synergistic antitumor effect in combination with 5FU or Raltitrexed

Abstract: Despite the introduction of several novel anticancer agents almost 50% of colorectal cancer (CRC) patients die for cancer suggesting the necessity of new therapeutical approaches. In this study we demonstrated that the HDAC inhibitor vorinostat exerted potent antiproliferative effect in a panel of mut-and wt-p53 human CRC cell lines. Moreover, in combination with 5-fluorouracil modulated by folinic acid (5FU-FA) or with Raltitrexed (RTX), both commonly used in the treatment of this disease, it showed a clear s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
99
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 66 publications
(107 citation statements)
references
References 35 publications
(57 reference statements)
8
99
0
Order By: Relevance
“…Furthermore, several clinical studies showed that the degree of inhibition of TS and the persistence of inhibition are essential factors for maximal in vivo growth inhibition by 5-FU [40,45]. Multiple in vitro investigations have shown an improved response to 5-FU with low level of TS protein and enzyme activity in cancer cells [26,[46][47][48]. The HDAC inhibitor vorinostat had been shown to enhance the efficacy of 5-FU through down-regulation of TS [47].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, several clinical studies showed that the degree of inhibition of TS and the persistence of inhibition are essential factors for maximal in vivo growth inhibition by 5-FU [40,45]. Multiple in vitro investigations have shown an improved response to 5-FU with low level of TS protein and enzyme activity in cancer cells [26,[46][47][48]. The HDAC inhibitor vorinostat had been shown to enhance the efficacy of 5-FU through down-regulation of TS [47].…”
Section: Discussionmentioning
confidence: 99%
“…Multiple in vitro investigations have shown an improved response to 5-FU with low level of TS protein and enzyme activity in cancer cells [26,[46][47][48]. The HDAC inhibitor vorinostat had been shown to enhance the efficacy of 5-FU through down-regulation of TS [47]. Sinomenine was also shown to have the ability to reduce the expression of TS mRNA and sensitize gastric cancer cells to 5-FU in vitro and in vivo [45].…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with our data, HDACIs (trichostatin-A and SAHA) were recently reported to downregulate TS and overcome 5-fluorouracil resistance in models of gastrointestinal malignancy. 53,54 Alternatively, the observed downregulation of TS and DHFR in ALL cell lines treated with SAHA or NaBu could result from the observed cell-cycle arrest induced by these agents rather than a direct effect on gene expression. Since no significant difference was found in the level of GGH mRNA expression and both FPGS and GGH activities determine the intracellular metabolism to MTX-PGs, we conclude that once MTX is inside the cells, accumulation of MTX-PGs is exclusively dependent on FPGS expression in cells treated with HDACIs.…”
Section: Discussionmentioning
confidence: 99%
“…SAHA causes changes in the promoter region of p21, whereas no change has been found in genes not regulated by SAHA, hence, suggesting selectivity in altering gene expression (154). SAHA also down-regulates expression of thymidylate synthase, consequently, exposure to SAHA prior to 5-FU induced synergistic effects between these two compounds in colorectal carcinoma cells (155). Increased acetylation levels of transcription factors (p53, HIF-1Į, E2F) and cytoplasmic proteins (Į-tubulin, cortacin, heat shock protein 90) may also contribute in SAHA-induced cell cycle arrest, cell death, and the inhibition of tumor growth seen in many xenograft models, although the specific mechanism of action is not known.…”
Section: Sahamentioning
confidence: 99%